(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2015)
The Common Skittering Frog, Euphlyctis cyanophlyctis was observed to inhabit in aquatic and semi-aquatic habitats with sparse vegetation covering cultivated lands, irrigation channels, marshes, ditches, domestic and derelict ponds, pools, puddles, wetlands, low lying areas, water logged areas, along the dikes or roads and towards the nearest sources of water. A total of 75 individuals was collected during the period from July, 2012 to June, 2013 from the village Bara Hazratpur, Mitapukur thana under Rangpur District and their food habits were studied. The average body weight of the frogs was 109.57 ± 23.05g and the average weight of the consumed food by each animal was 5.40 ± 3.65g with a variation between 0.1g and 13.3g which was 4.92% of their body weight. A total of 34 food items was found in the stomachs of 75 common skittering frogs. All the food items found in the stomachs were animal foods. The frogs fed mainly on insects (57.95%) that followed crustacean (13.89%), fishes (10.19), arachnids (9.36%), annelids (6.8%), amphibians (2.24%). The consumption of food varied seasonally, being much less in winter than in summer or rainy season. The percent frequency occurrence of insects in relation to the total number of food items was more or less same in all seasons. Insect food items were under18 families belonging to 10 orders, most of which are harmful to agriculture, gardens and human residences. So, education and awareness have been suggested through printed and electronic media regarding their contribution in maintaining ecological balance and role in ecosystem. The species should be conserved for maintaining natural balance and economy of the country. Asiat. Soc. Bangladesh, Sci. 41(1): 7-17, June 2015